Tungsten doped Bi1.5Zn0.92Nb1.5O6.92 ceramics designed as radio/microwave band pass/reject filters - (:unkn) unknown (WILEY, 2021)
Herein, radiowave/microwave bandpass/reject filters are fabricated from the tungsten doped Bi1.5Zn0.92Nb1.5-6x/5WxO6.92 (W-BZN) pyrochlore ceramics. The W-BZN band filters are prepared by the solid state reaction technique and subjected to X-ray diffraction (XRD) and impedance spectroscopy analyses. It was shown that the W-BZN filters can display negative capacitance effects accompanied with resonance-antiresonance oscillations. The calculations of the reflection coefficient parameter (S-11), the return loss (L-r) and the voltage standing wave ratios (VSWR) in the frequency domain of 0.01 to 1.80 GHz, has shown that the W-BZN device can perform as microwave cavities at two notch frequency values of 0.44 and 1.53 GHz. W-BZN devices can also be nominated as noise reducers and radiowave/microwave signal receivers suitable for telecommunication technology.
Keywords: band filters; Bi1.5Zn0.92Nb1.5-6x/5WxO6.92; ceramics; XRD; ELECTRICAL-PROPERTIES